2018
DOI: 10.4236/ajps.2018.93037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cluster Thinning on Quality of “Malbec” Grapes in Encruzilhada do Sul-RS

Abstract: The cultivar Malbec has been present's good performance and quality in the South Half of Rio Grande do Sul (RS). In this context, we aimed to evaluate the quality of "Malbec" grapes in relation to the phytotechnical, physicochemical parameters and bioactive compounds under different intensities of cluster thinning in Encruzilhada do Sul-RS. The experiment was carried out in a commercial vineyard in the 2015/16 with the cultivar Malbec (Vitis vinifera L.) under rootstock "1103 Paulsen", with spacing of 2.2 m be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…CT can increase total soluble solid concentration (TSS) (Reynolds et al, 1994;Valdes et al, 2009) and pH (Valdes et al, 2009) of the grape juice. It can also speed up ripening (Barros et al, 2018), which could be useful especially in regions with unfavourable conditions during grape ripening. This technique also increases ethylene production in some fruits, indicating advance maturity (Lopez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CT can increase total soluble solid concentration (TSS) (Reynolds et al, 1994;Valdes et al, 2009) and pH (Valdes et al, 2009) of the grape juice. It can also speed up ripening (Barros et al, 2018), which could be useful especially in regions with unfavourable conditions during grape ripening. This technique also increases ethylene production in some fruits, indicating advance maturity (Lopez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our meta-analysis revealed no overall signifcant increase in the concentration of anthocyanin and phenolics due to CT; however, many individual studies indicated a positive efect of CT on berry anthocyanin and phenolic concentration. Increases in anthocyanins were observed in studies performed in various wine regions that considered multiple varieties, including Nebbiolo [97], Tempranillo [51,[98][99][100][101], Syrah [100,102], Sangiovese [15], Grenache [91], Pinot Noir [10,34,46,103], Cabernet Sauvignon [27,32,39,46,104], Merlot [31], Malbec [36], Refosco [105], Tannat [92], and Cabernet Franc [8,104]. Te observed increases in grape and wine anthocyanin concentration might be determined by the increases in sugars determined by CT. Anthocyanin and sugar accumulation at the onset of ripening are strongly related [106]; however, uncoupling efects between anthocyanin and sugars may be observed during ripening when grapes are subjected to environmental stresses, such as drought or heat stress [107][108][109].…”
Section: Ct Regulates Production and Fruit Compositionmentioning
confidence: 99%
“…Reščič et al [42] also revealed a more consistent impact of thinning at 50% at reducing TA than 25%. Mota et al [39] compared 50% and 75% cluster thinning and showed no consistent pattern of either one treatment improving anthocyanin concentration across two years in Merlot, while in another study, thinning at 10%, 30%, and 50% increased anthocyanin concentration consistently [36].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The given fact relates to a looser arrangement of berries in the bunch, especially when using a cluster tipping method [6], [7]. A smaller grape crop improves grape ripening [8][9][10]. It can improve grape quality and wine quality parameters [11].…”
Section: Introductionmentioning
confidence: 99%